A preliminary survey of phytophagous mites and predaceous mites on some vegetable crops in Al-Jabal Al-Akhdar region, Libya - A.Kelah, Ommran; H.Amin, Adil H. (Al-Mukhtar Journal of Sciences, 2005)
This study was conducted in the northestern region of Al-jabal Al-Akhdar region, Libyan Arab Jamahiriya, to determine phytophagous mites. Eleven species were collected from vegetable crops, belonged to six genuses, six species of genus Tetranychus and one species for each of genuses : Tenuipalpus, Colomerus, Eriophyes, Aculops and Bryobia. On the otherhand four species of predaceous mites belonged to family phytoseiidae were collected on vegetable crops, Neosiulus steulus, Amblyseius swirski, phytoseiulus persimilis and Typhlodromus pyri. The results also showed that some vegetable crops were new hosts for phytophagous mites : colomerus vitis, Tenuipalpus granati and Bryobia sp